Effect of Venlafaxine on The Vitamins Contents of Saccharomyces Cerevisiae (NRRLY-12632) - Çakmak, Meltem; Özer, Dursun; Karatas, Fikret; Saydam, Sinan (My University, 2024)
In this study, Saccharomyces cerevisiae (NRLLY-12632) was grown in YPD medium containing different concentrations of Venlafaxine ((RS)-1-[2-dimethylamino-1-(4-methoxyphenyl)-ethyl] cyclohexanol). To counteract the effect of venlafaxine, vitamin C was added to the growth medium, and vitamins content of S. cerevisiae were investigated by HPLC. It was found that the amounts of water-soluble vitamins and lycopene concentration in S. cerevisiae, decreased with increased venlafaxine concentration compared to the control (p
Keywords: HPLC; vitamins; venlafaxine; S. cerevisiae